Candidate Oligo Therapeutic Target, miR-330-3p, Induces Tamoxifen Resistance in Estrogen Receptor-Positive Breast Cancer Cells via HDAC4 - Meng Zhang; Mei Wang; Zhiming Jiang; Ziyi Fu; Jingjing Ma; Sheng Gao (Hindawi-Wiley, 2023)
Tamoxifen is a drug used for treating breast cancer (BC), especially for individuals diagnosed with estrogen receptor-positive (ER+) BC. Its prolonged use could reduce the risk of recurrence and significantly lengthen the survival rate of BC patients. However, an increasing number of patients developed resistance to tamoxifen treatment, which reduced therapeutic efficiency and caused substandard prognosis. Therefore, the exploration of the molecular processes involved in tamoxifen resistance (TR) is urgently required. This investigation aimed to elucidate the relationship of microRNA-330 (miR-330-3p) with the TR of BC. There is little information on miR-330-3p's link with drug-resistant BC, although it is well known to regulate cell proliferation and apoptosis. Primarily, miR-330-3p expression in parental BC (MCF7/T47D), TR (MCF7-TR), and T47D/TR cell lines was detected by qRT-PCR. Then, the impact of miR-330-3p on the TR of BC cells was assessed by a cell proliferation assay. Lastly, dual-luciferase reporter, qRT-PCR, and western blot assessments were carried out to identify histone deacetylase 4 (HDAC4) as the potential miR-330-3p target gene. The data indicated that miRNA-330 was overexpressed in TR ER+ BC cells and its overexpression could induce TR. Furthermore, miRNA-330 could also reduce the expression of HDAC4, which is closely linked to TR, and overexpression of HDAC4 could reverse miRNA-330-induced drug resistance. In summary, miR-330-3p could induce TR of ER+ BC cells by downregulating HDAC4 expression, which might be a novel marker of TR and a possible treatment target against BC patients who are tamoxifen-resistant.